2018
DOI: 10.1063/1.5041990
|View full text |Cite
|
Sign up to set email alerts
|

The influence of anisotropic voxel caused by field of view setting on the accuracy of three-dimensional reconstruction of bone geometric models

Abstract: ARTICLES YOU MAY BE INTERESTED INMillimeter wave (220 GHz-330 GHz) characterizations of carbon nanotube films AIP Advances 8, 085110 (2018) The finite element method is playing an increasingly important role in osteoporosis screening. An accurate bone geometric model, a prerequisite for the finite element analysis, is affected by voxels. Isotropic voxel has advantages in three-dimensional reconstruction, but field of view setting usually results in anisotropic voxels. The main goal of this study was to investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Furthermore, some of the scans were acquired using isotropic sequences, and some were acquired using anisotropic imaging. A previous study has demonstrated that anisotropic voxels have a negligible effect on the 3D reconstruction of bone geometric models, and we do not believe they had an impact on our tendon models in the present study (10). We do not make any specific recommendations in regard to the optimal sequences to use, although logically sequences with high spatial resolution with narrow slice thickness and slice spacing, would be optimal for 3D reconstructions.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Furthermore, some of the scans were acquired using isotropic sequences, and some were acquired using anisotropic imaging. A previous study has demonstrated that anisotropic voxels have a negligible effect on the 3D reconstruction of bone geometric models, and we do not believe they had an impact on our tendon models in the present study (10). We do not make any specific recommendations in regard to the optimal sequences to use, although logically sequences with high spatial resolution with narrow slice thickness and slice spacing, would be optimal for 3D reconstructions.…”
Section: Discussionmentioning
confidence: 67%
“…High-resolution isotropic 3D (HiRes-3D) MRI acquisitions have isotropic, or near isotropic voxels as well as a slice thickness equivalent to in-plane resolution. Therefore, one of the primary advantages of HiRes-3D sequences when compared to traditional multiplanar 2D fast spin-echo (FSE) techniques is a reduction in partial volume averaging artifacts ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that 3D bone models can achieve high accuracy at the sub-millimeter scale, while increasing the voxel resolution (from 0.3 to 0.15 mm) does not improve the accuracy of the models ( 77 ). Our previous study ( 33 ) compared the accuracy of 3D bone models reconstructed with different anisotropic voxels (different pixel sizes) and found no significant differences in the linear, volume, and surface area measurements of the models. In particular, the linear measurement values remained highly consistent, indicating that pixel size had no significant influence on model accuracy at the submillimeter scale.…”
Section: Discussionmentioning
confidence: 97%
“…To test the influence of the reconstruction parameter setting on the consistency of reconstructed metatarsal geometric measurements, intraclass correlation coefficient (ICC) analysis was performed on the length, width, height, surface area, volume, and SA: V of 60 metatarsal bones from previous research ( 33 ), where the reconstruction parameter settings were the same as this study, and 60 metatarsal bones were scanned and reconstructed twice.…”
Section: Methodsmentioning
confidence: 99%